1980
DOI: 10.1128/aem.39.3.656-658.1980
|View full text |Cite
|
Sign up to set email alerts
|

New methods to assess bacterial injury in water

Abstract: Two methods are described for measurement of bacterial injury in water. Laboratory time preceding cell division measured with slide cultures and spheroplast formation after lysozyme treatment were accurate and rapid measurements of bacterial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The present study has demonstrated that a substantial proportion of E. coli cells subjected to either UVA or simulated sunlight become sublethally damaged, reaching a point where they can no longer form colonies in air on an agar-based medium. Following the approach of Zaske et al (1980), the relative percentage of such injured cells can be calculated by comparing the aerobic plate count for unsupplemented medium (uninjured cells) with the equivalent count for anaerobic, pyruvate-supplemented medium (injured plus uninjured cells). On this basis, c. 99% of the cells of E. coli NCTC 8912 subjected to simulated sunlight for a period of 6 h were sublethally damaged, being capable of forming colonies only under anaerobic, pyruvate-supplemented conditions and not under aerobic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has demonstrated that a substantial proportion of E. coli cells subjected to either UVA or simulated sunlight become sublethally damaged, reaching a point where they can no longer form colonies in air on an agar-based medium. Following the approach of Zaske et al (1980), the relative percentage of such injured cells can be calculated by comparing the aerobic plate count for unsupplemented medium (uninjured cells) with the equivalent count for anaerobic, pyruvate-supplemented medium (injured plus uninjured cells). On this basis, c. 99% of the cells of E. coli NCTC 8912 subjected to simulated sunlight for a period of 6 h were sublethally damaged, being capable of forming colonies only under anaerobic, pyruvate-supplemented conditions and not under aerobic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of chlorine-induced injury was determined from differential counts on tryptone lactose yeast extract (TLY) and TLYD (TLY with 0·1% deoxycholate) agar plates (Zaske et al 1980). Both types of plates were inoculated, incubated, and counted as described above.…”
Section: Viable Plate Counts and Injury Assessmentmentioning
confidence: 99%
“…Flint (1987) showed that in the absence of other bacteria, i.e. in the absence of competitors, in sterile autoclaved river water E. coli could Discussion survive for up to 260 d, even at 2 5 T , without The factors which are considered most likely to any decline in numbers and without suffering affect the survival of non-indigenous bacteria in any of the apparent stress symptoms seen by others (Bissonnette et al 1975(Bissonnette et al , 1977Zaske et al 1980). As expected, the addition of a complex mixture of nutrients, in the form of synthetic sewage, to filtered-autoclaved lake water allowed the E. coli to increase in numbers in proportion to the amount of synthetic sewage added.…”
Section: N I T R O G E N a D D I T I O N Smentioning
confidence: 99%